Bond dissociation energies of carbonyl gold complexes: a new descriptor of ligand effects in gold(i) complexes?. Issue 43 (19th October 2018) - Gatineau, David; Lesage, Denis; Clavier, Hervé; Dossmann, Héloïse; Chan, Chen H.; Milet, Anne; Memboeuf, Antony; Cole, Richard B.; Gimbert, Yves
Abstract : A new experimental method using mass spectrometry was developed to evaluate ligand electronic effects on gold(i ) complexes. Abstract : Ligand electronic effects in gold(i ) chemistry have been evaluated by means of the experimental determination of M–CO bond dissociation energies for 16 [L–Au–CO] + complexes, bearing L ligands widely used in gold catalysis. Energy-resolved analyses have been made using tandem mass spectrometry with collision-induced dissociation. Coupled with DFT calculations, this approach enables the quantification of ligand effects based on the LAu–CO bond strength. A further energy decomposition analysis gives access to detailed insights into this bond's characteristics. Whereas small differences are observed between phosphine- and phosphite-containing gold complexes, carbene ligands are shown to stabilize the gold-carbonyl bond much more efficiently.